Marine parasites as biological tags in South American Atlantic waters, current status and perspectives - Cantatore, Delfina María Paula (2013)
Many marine fisheries in South American Atlantic coasts (SAAC) are threatened by overfishing and under serious risk of collapsing. The SAAC comprises a diversity of environments, possesses a complex oceanography and harbours a vast biodiversity that provide an enormous potential for using parasites as biological tags for fish stock delineation, a prerequisite for the implementation of control and management plans. Here, their use in the SAAC is reviewed. Main evidence is derived from northern Argentine waters, where fish parasite assemblages are dominated by larval helminth species that share a low specificity, long persistence and trophic transmission, parasitizing almost indiscriminately all available fish species. The advantages and constraints of such a combination of characteristics are analysed and recommendations are given for future research. Shifting the focus from fish/parasite populations to communities allows expanding the concept of biological tags from local to regional scales, providing essential information to delineate ecosystem boundaries for host communities. This new concept arose as a powerful tool to help the implementation of ecosystem-based approaches to fisheries management, the new paradigm for fisheries science. Holistic approaches, including parasites as biological tags for stock delineation will render valuable information to help insure fisheries and marine ecosystems against further depletion and collapse.